THE IMPORTANCE OF SCHOOL GUIDANCE ACTIVITIES IN THE CONTEXT OF THE NECESSITY OF KNOWING THE VOCATIONAL INTERESTS IN A DYNAMIC EUROPE - Maria-Elena, GHEORDUNESCU; Laura-Filofteia, PANOIU (Strategii Manageriale, 2014)
Strategy Europe 2020 aims to ensure an economic growth: smart, more efficient throught investment in education, reseatch and innovation; durable, by decisive orientation to a new economy with low-emisions of carbon dioxide and favorable to inclusion, by focusing on creating jobs and redcuing poverty. The priorites of the strategy will be achieved through five objectives, one which is linked to emplyment, namely: employment rate of 75% for population aged between 20 and 64 years. Providing such rate of occupancy implies policies at microeconomical level, but we consider also at individual level. So the young, future employees must be properly trained, and have the right to be able to handle a job. Current realities show that employers are interested in having by their side in accomplishing their goals, employees who are proactive, who improvise, who can cope with various demands in which they are involved, and respond positively to companies. They require a career choice to meet the vocational interests. Based on these issues, this paper aims to analyze the importance of knowing the vocational interests in school orientation by highlighting the correlation between the selected profile and personality of each. However, in this paper we try to show that school guidance is an early process and that if they knew their vocational interests, young people would be more decisive in the choice of future profession. We believe that, if the counseling activites and school oriantation would be conducted in a professiona way, youth might focus on those occupations which best define them and also could access appropriate university programs with favorable effects on employment levels.